2007
DOI: 10.1021/jp075300i
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Aerosol Substrate in the Heterogeneous Ozonation Reactions of Surface-Bound PAHs

Abstract: To probe how the aerosol substrate influences heterogeneous polycyclic aromatic hydrocarbon (PAH) oxidation, we investigated the reaction of surface-bound anthracene with gas-phase ozone on phenylsiloxane oil and azelaic acid aerosols under dry conditions in an aerosol flow tube with offline analysis of anthracene. The reaction exhibited pseudo-first-order kinetics for anthracene loss, and the pseudo-first-order rate coefficients displayed a Langmuir-Hinshelwood dependence on the gas-phase ozone concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
161
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(188 citation statements)
references
References 34 publications
23
161
4
Order By: Relevance
“…About 0.2 g azelaic acid used to generate nucleus is put in a small boat-shaped ceramic container positioned at the center of the first quartz tube. Azelaic acid is chosen as the nucleus because it has little reactivity with ozone (Kwamena et al, 2007). The temperature of the first quartz tube is set at 413 K. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…About 0.2 g azelaic acid used to generate nucleus is put in a small boat-shaped ceramic container positioned at the center of the first quartz tube. Azelaic acid is chosen as the nucleus because it has little reactivity with ozone (Kwamena et al, 2007). The temperature of the first quartz tube is set at 413 K. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…They also revealed that some of the reaction products included surfacebound ketone, lactone, and anhydride groups. Other research teams extended this work to specific surface-bound compounds (including polycyclic aromatics, 43,[53][54][55][56][57][58] biogenic volatile organics, 59 biomass burning products, 60 and fungicides 61 ) and functionalities at well-characterized aerosol surfaces. [62][63][64][65][66] Within the body of literature on O 3 reactions with aerosols, investigations of the ozonolysis of oleic acid aerosols are of particular interest because these particulates appear in relative high abundance in certain regions of the atmosphere.…”
Section: à7mentioning
confidence: 99%
“…Two tandem 3 cm (outer diameter) Â 40 cm (length) quartz tubes heated with heating tapes were used as an aerosol generator. Azelaic acid was chosen as the model nucleus because it was almost inert to ozone (Kwamena et al, 2007). A small ceramic container containing w0.4 g azelaic acid was positioned at the center of the first tube.…”
Section: Heterogeneous Reaction Experimentsmentioning
confidence: 99%